2012
DOI: 10.1186/2110-5820-2-38
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a neonatal pain management module in the computerized physician order entry system

Abstract: BackgroundDespite the recommended guidelines, the neonatal management of pain and discomfort often remains inadequate. The purpose of the present study was to determine whether adding a pain and discomfort module to a computerized physician order entry (CPOE) system would improve pain and discomfort evaluation in premature newborns under invasive ventilation.MethodsAll newborns <37 weeks gestational age (GA) and requiring invasive ventilation were included in a prospective study during two 6-month periods: bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…In paediatrics, two recent studies reported controversial results about the accuracy of dynamic variables derived from the plethysmographic waveform to predict fluid responsiveness for mechanically ventilated patients under general anaesthesia (21,22). In neonatology, a median PVI value of 20 (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)% was recently reported in spontaneously breathing-term neonates on the first day of life, mainly influenced by the behavioural status of the newborn (23). Our study is the first to record PVI values in premature neonates during IPPV, but these conditions did not result in major differences regarding the PVI data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In paediatrics, two recent studies reported controversial results about the accuracy of dynamic variables derived from the plethysmographic waveform to predict fluid responsiveness for mechanically ventilated patients under general anaesthesia (21,22). In neonatology, a median PVI value of 20 (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)% was recently reported in spontaneously breathing-term neonates on the first day of life, mainly influenced by the behavioural status of the newborn (23). Our study is the first to record PVI values in premature neonates during IPPV, but these conditions did not result in major differences regarding the PVI data.…”
Section: Discussionmentioning
confidence: 99%
“…Plethysmographic variability index was 22 (18)(19)(20)(21)(22)(23)(24)(25)(26)(27). None of the perinatal characteristics listed in Table 1, including postnatal age, had a significant influence on PVI.…”
Section: Echocardiographic Datamentioning
confidence: 99%
“…Of the studies, five described electronic health record systems (11)(12)(13)(14)(15), 11 CPOE (16-26), 17 CDS systems (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43), six surveillance systems or "sniffers" (44)(45)(46)(47)(48)(49), and six electronic medication reconciliation tools not fitting into the prior categories (50)(51)(52)(53)(54)(55). Almost all of the studies were peri-implementation designs comparing preintervention with postintervention.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Of the studies addressing ICU mortality as an endpoint, there were four using CPOE systems (17,19,20,23), three CDS (30,34,40), and two sniffers (46,47). Heterogeneity was high in all subgroups and none trended toward a significant effect.…”
Section: Mortalitymentioning
confidence: 99%
See 1 more Smart Citation